PS2 - 174 Hexokinase 2 Drives Radio-Resistance through ERK Signaling and Sensitizes Cells to Azole Compounds. (18th October 2016) - Agnihotri, S.; Li, M.; Wilson, M.R.; Burrell, K.; Alamsahebpour, A.; Aldape, K.; Zadeh, G.
Abstract : Our ongoing work has demonstrated that hexokinase 2 (HK2) but not HK1 or HK3 is a critical mediator of tumour glycolysis and mitochondrial metabolism in Glioblastoma (GB). Furthermore, HK2 is highly expressed in GB but not in normal brain making it an attractive therapeutic target. Our current findings now support that loss of HK2 alters tumor vasculature, increases sensitivity to radiation, and confers a significant survival benefit in several GB xenograft-bearing mice. Using a genome wide transcript analysis, we identified that loss of HK2 attenuates several pro-growth signaling pathways in GB including ERK signaling. Mechanistically, ERK rescue experiments in HK2 depleted cells rescues cell sensitivity to radiation and reduces DNA damage. Furthermore using a systems biology approach and a rationale drug screen we identified several antifungal agents in the azole class as to inhibit tumor metabolism and growth in HK2 expressing GB cells. Loss of HK2 in GB cells dampened the effect of several azoles suggesting that the mechanism of action is mediated in part through HK2. Furthermore, we tested several azole compounds known to cross the blood brain barrier in vivo. Clinically achievable doses of azoles as single agents increased survival in several orthotopic xenograft GB mouse models. In summary, HK2 drives several oncogenic pathways associated with GB including ERK signaling and sensitizes tumour cells to the azole class of antifungals. Future work will determine whether azoles work synergistically with radiation and temozolomide and elucidate the mechanisms by which they inhibit GB growth in HK2 expressing cells.